Early Theories of Punishment: Deterrence, Rehabilitation and Restoration in Ancient Greek and Indian Penology - Linderborg, Otto (Law, crime & history, 2024)
This study examines ancient penology, focusing on literary sources from ancient Greece and India as the primary material for analysis. The theories of punishment encountered in these texts are analysed by applying theoretical concepts of modern penology. The study indicates that attempts to rationalize punishment and provide alternatives to traditional retributive and deterrent approaches to penology date back far earlier than is commonly presumed, specifically to the axial age in Greece and India (800-200 BCE).